Impacto sensorial da microbiota no off-flavour da cerveja artesanal Session Ipa durante o armazenamento - Araújo, Francisca Raquel Vieira de (2019)
The preference of today's consumers has changed compared to a beer industry, since there is a growing demand for craft beers, which can be found in a set of full-bodied flavors and aromas. The term off-flavor is used to determine an unpleasant, unpleasant taste in the beverage resulting from the chemical or microbiological degradation of the components of the beverage during its processing or storage. The aim of this research is of the research was to evaluate the deteriorating microbiota present in the Craft Beer Session IPA and its impact on the production and stability of off-flavors during its storage for 150 days under two temperature conditions, and to verify the behavior of the antioxidant activity and of the total phenolic compounds content. Microbiological, sensorial and chemical analyzes were performed at the date of packing (T0) and at 30 day intervals (T30, T60, T90, T120 and T150) for the beers stored at temperatures of 18°C (A) and 1°C (B). For the quantification of the deteriorating microbiota of the beer, the counts of lactic and acetic bacteria, yeasts Saccharomyces and not Saccharomyces were carried out by the methodology of filtration in membrane. The hedonic thresholds (MLH) methodology was applied in the determination of compromised acceptance (LAC) and rejection (LR) thresholds. The Check-All-That-Apply (CATA) method was applied to understand how the consumer describes craft beer. The methodology of the DPPH and ABTS radicals, in the determination of the antioxidant capacity of the beer, and for its content of total phenolic compounds, the Folin-Ciocalteau method was used. There was no growth of lactic and acetic bacteria during storage for samples A and B. But, there was growth of Saccharomyces yeasts, except in T30 (A), and not Saccharomyces, except in T30 and T120 (A) and in T150 (B ). With high counts for yeasts Saccharomyces and not Saccharomyces in T60 (A) and T120 (B). The LAC were identified for sample B attributes overall impression (T60) and flavor (T60). LR was identified for the flavor attribute (T60) only in sample B. The antioxidant activity of the samples did not change over time. However, there was an indication that total phenolic compounds changed over time. In the research, a possible association between the high yeast load and the appearance of the LAC of the samples was observed.